Tenage Pregnancy - Ariawan Soejoenoes (Indonesian Socety of Obstetrics and Gynecology, 2017)
Sexual activity among teenagers has been increasing over the past decade, accompanied by younger age at first intercourse which is associated with inconsistent or nonuse of contraception. Problems become more complex because the onset of puberty is earlier than before and sociocultural and religious norm are less stringent, leading to greater opportunities to have pre-marital sex.1 Between 2011 and 2020, more than 140 million girls will become child brides, according to the United Nations Population Fund (UNFPA).2 If current levels of child marriages hold, 39.000 girls daily will marry too young.1